Implementasi Kebijakan Peraturan Pemerintah Nomor 11 Tahun 2017 Berbasis Paperless pada Badan Kepegawaian Daerah dan Pengembangan Sumber Daya Manusia Kota Medan - Febrita Rahayu; Budi Hartono; Maksum Syahri Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this research is to analyze the implementation and identify the driving and inhibiting factors of the implementation of Government Regulation Number 11 of 2017 on Paperless Civil Servant Rank Promotion Services at the Regional Personnel Agency and Human Resource Development of Medan City by applying Edward III's theory. This study used a descriptive qualitative approach with data collection techniques of observation, interviews, and documentation. The data analysis technique used in this study consisted of four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the study showed that the implementation of Government Regulation Number 11 of 2017 on Paperless Civil Servant Rank Promotion Services at the Regional Personnel Agency and Human Resource Development of Medan City is still not optimal due to (1) the suboptimal application of service-oriented work culture values, (2) the low interest of civil servants in applying for rank promotion during the COVID-19 pandemic, and (3) the development of the personnel information system is not fully capable of producing accurate information. The Regional Personnel Agency and Human Resource Development of Medan City is trying to run paperless rank promotion services by optimizing the SAPK and SIASN systems so that employee data is integrated for effective and efficient services in the future.